Legal Analysis Of Criminal Liability For Identity Falsement By A Fiduciary Agent - Irma Ramadani; Hambali Thalib; Dian Eka Pusvitas Azis (HORIZON PUBLIC LEGAL STUDIES, 2025)
This research aims to determine and analyze the qualifications of the criminal act of identity forgery in a fiduciary agreement and to determine the legal considerations of the judge in making a decision in the case of Decision No. 1097 / Pid.sus / 2019 / PN. Mks. This research was conducted with a normative legal research type that uses secondary legal materials or is a study by taking several books, journals or references related to the research. The results of this study indicate that (1) The qualifications of the criminal act of identity forgery in a fiduciary guarantee agreement are the requirements that must be met in order to be categorized as a crime. Forgery is the act of replacing a letter or document carried out by an individual or group of individuals. The act of forgery is a crime characterized by a framework of falsehood or fraud against an object. Fraud is an act carried out intentionally to deceive or manipulate others for personal or group interests. Thus in this case or case No. 1097 / Pid.Sus / 2019 / PN. Mks certainly meets the requirements as a criminal act. (2) Legal analysis of the judge's decision in case No. 1097/Pid.Sus/2019/PN. Mks Regarding Identity Forgery in Fiduciary Guarantees is that the defendant has fulfilled the elements of Article 263 paragraph (1) of the Criminal Code and the elements of Article 36 of Law No. 42 of 1999 Concerning Fiduciary Guarantees. The recommendation of this study is that as law enforcement officers in determining the qualifications of criminal acts, they must be more careful in finding the elements of their actions, whether the action is a criminal act (criminal law) or a civil act (civil law) so as not to make a mistake in prosecution, and as the owner of the fiduciary object guarantee or in this case companies engaged in the fiduciary sector to be more detailed and careful when agreeing to provide fiduciary objects so that it does not happen again as in the case explained above.